Palms, Botanical Gardens, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
This postcard shows a pathway lined with palm trees in the Botanical Gardens, Port of Spain, Trinidad.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1910]; Gardens--Trinidad and Tobago; Garden walks--Trinidad and Tobago